A New Evapotranspiration Model Accounting for Advection and Its Validation during SMEX02. (12th December 2013) - Yang, Yongmin; Su, Hongbo; Zhang, Renhua; Wu, Jianjun; Qi, Jianwei
Abstract : Based on the crop water stress index (CWSI) concept, a new model was proposed to account for advection to estimate evapotranspiration. Both local scale evaluation with sites observations and regional scale evaluation with a remote dataset from Landsat 7 ETM+ were carried out to assess the performance of this model. Local scale evaluation indicates that this newly developed model can effectively characterize the daily variations of evapotranspiration and the predicted results show good agreement with the site observations. For all the 6 corn sites, the coefficient of determination (R 2 ) is 0.90 and the root mean square difference (RMSD) is 58.52W/m 2 . For all the 6 soybean sites, theR 2 and RMSD are 0.85 and 49.46W/m 2, respectively. Regional scale evaluation shows that the model can capture the spatial variations of evapotranspiration at the Landsat-based scale. Clear spatial patterns were observed at the Landsat-based scale and are closely related to the dominant land covers, corn and soybean. Furthermore, the surface resistance derived from instantaneous CWSI was applied to the Penman-Monteith equation to estimate daily evapotranspiration. Overall, results indicate that this newly developed model is capable of estimating reliable surface heat fluxes using remotely sensed data.